Rice Trade and Its Alignment with National Law (Case: Regency of Sidenreng Rappang) - Bunyamin, Bunyamin; Mujahidin, Mujahidin; Agit, Alamsyah (CV. Utility Project Solution, 2023)
This paper explores Indonesian rice trade issues like asymmetric knowledge, unethical competition, and price fluctuation. Agriculture generally favors asymmetric knowledge. Unethical competitors hurt other producers. Unhusked rice prices fell, harming farmers. Researching Indonesian legal rules and norms and their implementation in human behavior solved these problems using a normative-empirical method. The paper advises setting distribution agents, marketing targets, and regular harvest pricing to improve farmer welfare. The paper strongly suggested the government rice quality support. It emphasizes data accuracy for company performance and competitive advantage. The paper proposes choosing distribution agents and marketing targets to minimize unethical producer competition. Price fluctuation and business owners' refusal to pay are examined in Indonesia's rice trade. A farm-level grain marketing system review would assist farmers. The result of this paper also noted Sidenreng Rappang Regency vendors and rice millers' unfair pricing. Indonesian farmer welfare strategies are studied. It recommends finding reliable distributors and marketing targets and keeping pricing consistent during harvest season. Producer-buyer understanding reduces unethical competition. The paper examines Indonesia's rice collectors. Farmers need stable agricultural prices. Further, emphasizing addressing dealers' and rice millers' harmful price practices. This study concludes that Indonesian rice trading concerns include asymmetric information